Estrategias de uso del gas natural que disminuyan la contaminación por dióxido de carbono mediante la revisión de un sistema de gestión integral energética (2018)
This monograph aims to establish strategies for the reduction of CO2 emissions through the use of natural gas, following the guidelines of a comprehensive energy management system (SGIE), this was reviewed in Colombia, based on ISO 50001 and the regulatory framework. Subsequently, a strategic analysis of the use of natural gas in Colombia was made through applied and successful experiences that allow the reduction of carbon dioxide emissions. Likewise, a detailed description was made of all the characteristics of natural gas in order to identify its benefits and disadvantages.